The impact of concomitant infective endocarditis in patients with spondylodiscitis and isolated spinal epidural empyema and the diagnostic accuracy of the modified duke criteria - Hijazi, Mido Max; Siepmann, Timo; El-Battrawy, Ibrahim; Aweimer, Assem; Schröttner, Percy; Mirus, Martin; Podlesek, Dino; Schackert, Gabriele; Juratli, Tareq A.; Eyüpoglu, Ilker Y.; Filis, Andreas (Frontiers in Surgery, 2024)
The co-occurrence of infective endocarditis (IE) and primary spinal infections (PSI) like spondylodiscitis (SD) and isolated spinal epidural empyema (ISEE) has been reported in up to 30% of cases and represents a life-threatening infection that requires multidisciplinary management to be successful. Therefore, we aimed to characterize the clinical phenotypes of PSI patients with concomitant IE and furthermore to assess the accuracy of the modified Duke criteria in this specific population.We conducted a retrospective cohort study in consecutive SD and ISEE patients treated surgically at our University Spine Center between 2002 and 2022 who have undergone detailed phenotyping comprising demographic, clinical, imaging, laboratory, and microbiologic assessment. Comparisons were performed between PSI patients with IE (PSICIE) and without IE (PSIWIE) to identify essential differences.Results: Methicillin-susceptible Staphylococcus aureus (MSSA) was the most common causative pathogen in PSICIE group (13 patients, 54.2 %) and aortic valve IE was the most common type of IE (12 patients, 50%), followed by mitral valve IE (5 patients, 20.8%).